Prospective, double-blind diagnostic multicentre study of confocal laser endomicroscopy for wheat sensitivity in patients with irritable bowel syndrome. Issue 8 (20th September 2021) - Bojarski, Christian; Tangermann, Paul; Barmeyer, Christian; Buchkremer, Juliane; Kiesslich, Ralf; Ellrichmann, Mark; Schreiber, Stefan; Schmidt, Carsten; Stallmach, Andreas; Roehle, Robert; Loddenkemper, Christoph; Daum, Severin; et al.
Abstract : Objective: A considerable proportion of patients with irritable bowel syndrome (IBS) may be wheat-sensitive and respond to a gluten-free diet (GFD) although they do not have coeliac disease. However, a diagnostic test for wheat sensitivity (WS) is missing. Our study evaluated the diagnostic accuracy (sensitivity and specificity) of confocal laser endomicroscopy (CLE) for the identification of WS as primary outcome. Design: In this prospective, double-blind diagnostic study 147 non-coeliac patients fulfilling the Rome III criteria for IBS were tested by CLE for duodenal changes after wheat (index test), soy, yeast or milk exposure. Patients with IBS responding to 2 months of GFD were classified as having WS (reference test) using response criteria recommended by regulatory bodies for pharmaceutical trials of patients with IBS. After 2 months, CLE results were unblinded and patients were advised to exclude those food components that had led to a positive CLE reaction. The clinical response was assessed at follow-up after 6 and 12 months. Results: Of 130 patients who completed the study per protocol, 74 (56.9%) responded to GFD and were classified as WS after 2 months, and 38 of these 74 patients were correctly identified by CLE (sensitivity 51.4%; 97.5% CI: 38.7% to 63.9%). A total of 38 of 56 patients without WS were correctly identified by CLE (specificity 67.9%; 97.5% CI: 52.9% to 79.9%). At 6 months follow-up, CLE correctly identified 49 of 59 food-sensitive patients (sensitivity 83.1%; 97.5% CI: 69.9% to 91.3%) but specificity was only 32% (97.5% CI: 15.7% to 54.3%). Conclusion: In light of the high proportion of patients with IBS responding to GFD, the diagnostic accuracy of CLE is too low to recommend widespread use of this invasive procedure. Trail registration number: This study was registered as clinical trial in the German Registry for Clinical Studies (DRKS00010123).